Ultrashort pulse laser processing of silica at high repetition rates—from network change to residual strain - Zimmermann, Felix; Lancry, Matthieu; Plech, Anton; Richter, Soeren; Ullsperger, Tobias; Poumellec, Bertrand; Tuennermann, Andreas; Nolte, Stefan (International Journal of Applied Glass Science, 2017)
We report on the analysis of silica-based glasses after processing with ultrashort laser pulses at high repetition rates. Heat accumulation leads to strong local heating of the glass. The subsequent quenching results in a fictive temperature rise that scales with the repetition rate. Consequently, the relative volume change leads to residual tensile strain within the modified volume of larger than 10−3, which is confirmed by wide-angle X-ray scattering (WAXS) measurements. Studying the surface topography after cleaving of laser-modified regions allows for quantification of the corresponding elastic strain as well as the glass density behavior on the fictive temperature.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Raman spectroscopy - characterization; silicate - glass forming systems; x-ray scattering - characterization